Borrowing for College: A Comparison of Long‐Term Debt Financing between Public and Private, Nonprofit Institutions of Higher Education1. (June 2014) - Denison, Dwight; Fowles, Jacob; Moody, Michael J.
<x xml:space="preserve">Abstract</x> Institutions of higher education provide an excellent opportunity to compare long‐term debt financing in the nonprofit and public sectors. The proposed models explain the long‐term debt per student at public and private‐nonprofit research universities. Student enrollment, enrollment growth, total assets, and revenue variables as a group all influence debt levels. The strongest predictors of debt balances are the fixed characteristics of the universities themselves. Empirical evidence from the university sector also suggests the absence of a powerful arbitrage incentive to issue debt.